A bioinspired multilegged soft millirobot that functions in both dry and wet conditions - Haojian Lu (Nature Portfolio, 2018)
Despite the enormous potential of magnetically-guided soft robots for various applications, challenges related to inefficient locomotion in harsh environments hinder its development. Here, the authors demonstrate a multi-legged millirobot with excellent locomotion capability in harsh environments.